Gastric dilatation and chronic gastritis in one-month-old puppy - Mehmet Maden; Aliye Sağkan Öztürk; Hasan Güzelbekteş (Eurasian Journal of Veterinary Sciences)
The puppy was one-month-old and male when it was admitted to the Department of Internal Medicine at the Faculty of Veterinary Medicine, University of Selcuk, Konya-Turkey. In this report, it was evaluated that the approaches of diagnosis and treatment of a case of gastric dilatation and chronic gastritis defined on the basis of clinical, laboratory, radiographic and endoscopic findings in an English Bulldog puppy. The presenting complaints were anorexia, dullness, abdominal distention, nausea, attempts to vomit and defecate, colic, constipation, praying position and neurologic seizures. Bilateral abdominal distention, colic and evidence of gastric pain were found on clinical examination of the dog. The owner informed that the dog had been feeding dry dog food for adult dog and overeating. Edema and thickness, increased mucus, hyperemia, mucosal fragility and sensitivity in the rugal folds of curvature major, petechiel bleeding, and bile retention together with mucosal degeneration were observed by the endoscopic examination in the puppy. Gastric dilatation and chronic gastritis were diagnosed on the basis of clinical, laboratory, radiologic and endoscopic findings and was treated. In conclusion, it was decided that the case could be a result of falsely feeding. We recommend the gastric decompression and lavage along with the use of sedative and fluid therapy in the treatment of the cases.